Characteristics of Qualitative Descriptive Studies: A Systematic Review. Issue 1 (30th September 2016) - Kim, Hyejin; Sefcik, Justine S.; Bradway, Christine
Abstract: Qualitative description (QD) is a term that is widely used to describe qualitative studies of health care and nursing‐related phenomena. However, limited discussions regarding QD are found in the existing literature. In this systematic review, we identified characteristics of methods and findings reported in research articles published in 2014 whose authors identified the work as QD. After searching and screening, data were extracted from the sample of 55 QD articles and examined to characterize research objectives, design justification, theoretical/philosophical frameworks, sampling and sample size, data collection and sources, data analysis, and presentation of findings. In this review, three primary findings were identified. First, although there were some inconsistencies, most articles included characteristics consistent with the limited available QD definitions and descriptions. Next, flexibility or variability of methods was common and effective for obtaining rich data and achieving understanding of a phenomenon. Finally, justification for how a QD approach was chosen and why it would be an appropriate fit for a particular study was limited in the sample and, therefore, in need of increased attention. Based on these findings, recommendations include encouragement to researchers to provide as many details as possible regarding the methods of their QD studies so that readers can determine whether the methods used were reasonable and effective in producing useful findings. © 2016 Wiley Periodicals, Inc.